Develop Electricity Projects and Transmission lines in a 'War Footing' - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not available. DOI: http://dx.doi.org/10.3126/hn.v14i0.11243 Hydro Nepal Journal Journal of Water, Energy and Environment Vol. 14, 2014, January Page:7-7